A multi‐factor approach to assessing the socio‐economic and metropolitan environmental development of border areas in the Central Black Soil Region of Russia (Belgorod, Voronezh and Kursk regions) in order to develop a model concept - N. V. Yakovenko; N. V. Chugunova (Юг России: экология, развитие)
Aim. The aim is to assess the socio‐economic and metropolitan environmental  development  of  border  areas  of  the  Central  Black  Soil region (Belgorod, Voronezh, Kursk regions) in order to develop a model concept.Material and Methods. The study uses a systematic approach through methods of comparative and economic‐statistical analysis. The statistical base employed was the official materials of Rosstat 2016–2020.Results. The calculated integral index of socio‐economic and metropolitan environmental development of the border areas of the Central Black Soil region indicates the presence of four groups of municipalities with high, medium, below average and low levels of development. The socio‐ economic development of border areas is characterised by high spatial heterogeneity and a high degree of concentration of human and economic capital within the agglomerations. There is a polarisation in the considered indicators: while the gap in the private indices is not so significant, it is significant between municipalities. In accordance with our calculations, there is a need to develop a model concept of socio‐economic and metropolitan environmental development of border regions.Conclusions. The level of socio‐economic development of areas is a derivative of the power generated by the metropolitan‐core and is determined by the available local economic potential, the ability of district centres of concentration of business activity to absorb the impacts of the metropolitan centre. Gradual "filling" of socio‐economic gaps is possible if the level of development of the metropolitan core and adjacent territories increases, i.e. the territorial spread of the positive socio‐economic effects generated by the metropolis.The work has solved an urgent practice‐oriented task of socio‐economic and geographical research – the assessment of socio‐economic and metropolitan environmental development of border areas of the Central Black Soil region, which provides an opportunity to comprehensively and adequately identify "strengths and weaknesses" of the metropolitan development of the regions.